Differential Analysis of Personality Disorders and Affective Disorders - Zinchenko, Yuliia (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2025)
The article considers the problem of differential differences between severe personality disorders and affective spectrum disorders. A comparative analysis of symptoms, behavioral manifestations, and features of the development of these disorders is conducted. The leading differences in the structure of personality functioning are identified, as well as common internal mental processes inherent in both personality and affective disorders. Severe personality disorders of the borderline level of organization are characterized by a stable diffusion of identity in the personality structure, which is associated with traumatic or stressful conditions of development and disintegration of emotional experience. Affective spectrum disorders are determined by neurobiological disorders in mental functioning, which determine the periodicity of the occurrence of affective disorders and are associated with both genetic factors and stressful experience. Cognitive disorders of affective stimuli volitional control are defined as internal mental processes inherent in both personality and affective disorders, which determine the similarity of their symptoms and behavioral manifestations. Based on the results of the comparative analysis, it is proposed to consider the diffusion of identity in the structure of an adult personality as a differential sign of severe personality disorders. The article will be useful for practicing psychologists and psychotherapists who face difficulties in conducting differential diagnostics of severe personality disorders of the emotionally unstable type.